PENERAPAN METODE DISKUSI UNTUK MENINGKATKAN HASIL BELAJAR SISWA PADA MATERI ORGANISASI - Jayus Jayus (HUMANIS: Jurnal Ilmu-Ilmu Sosial dan Humaniora, 2017)
The study aimed to describe the implementation of discussion method in learning of PKn lesson on the material of organizaion and to know its influence in order to improve the students’ achievement. The study used Classroom Action Research method with two cycles. Each cycle consisted of four phases, those are planning, action, observation, and reflection. The data collection was done using students observation sheet and achievement test in each cycle. Furthermore, the data was analyzed by quantitative and qualitative analysis. The study result could be seen from the presentation of the students activity average at thefirst cycle that is 69 in moderate active category and has been improving at the second cycle to be 81 in active category. The students completness at the first cycle only 6 students (62%) and has been improving at the second cycle to be 8 students (100%). The conclusion of the study showed that the implementation of discussion method can improve the students achievement at the learning of PKn lesson on the material of Organization.